Upaya Peningkatan Motivasi Belajar Siswa Dengan Pendekatan Inquiry Pada Pelajaran Fisika Kelas Xi Multimedia Semester 1 SMK N 1 Gunung Talang Kecamatan Gunung Talang Kabupaten Solok - Yardi Yardi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2015)
The students learning process is necessary in learning and teaching process because the result of the lesson determined by the process that the students got.Recording to this, the researcher was interested in conducting a study about the improvement of the students motivation in learning by using inquiry approach in physic at grade XI MULTIMEDIA term one SMKN 1 Gunung Talang. The method used in this study was decriptive with percent data analysis technique. The results of the study informed: [1].The using of inquiry approach in physic learning could increase students, [2].The motivation implementation and their grade of inquiry approach is one of the solution to overcome to the the low students motivation in learning.